dan STUDI ZONA ALTERASI HIDROTHERMAL DAERAH SUMI DAN SEKITARNYA, KECAMATAN LAMBU, KABUPATEN BIMA PROPINSI NUSA TENGGARA BARAT - Habib Juhair Al Habib (Retii, 2020)
ABSTRACT Geologically, the Sumi area and its surroundings contain volcanic igneous rocks which are the products of old volcanoes that are lower Miocene in age. The age of the volcano is considered sufficient in the geological time scale to form hydrothermal alteration. The presence of volcanic rocks that form the dyke and sill structures at the research location indicates that volcanism has taken place. Generally, volcanism is closely related to hydrothermal alteration processes. Thus the Sumi area is very interesting to study further regarding the existence of developing hydrothermal alterations. The purpose of this study is to determine the altration zone that develops at the research location. The method used is in the form of literature studies, field surveys and petrographic analysis to determine the constituent minerals. In the research location, it can be concluded that LP 1 is associated with the alteration zone: prophylitic with andesite wall rocks. The LP 2 alteration zone is a phyllite alteration zone with unknown wall rocks. The LP 3 alteration zone is the outer prophylitic - argillic zone with unknown wall rocks. The LP 4 altration zone is a prophylitic alteration zone with unknown wall rocks. Keyword : Alteration, Hidrothermal, Sumi, Bima